SWEAT CONDUCTIVITY IN THE DIAGNOSIS OF CYSTIC FIBROSIS - THE EXPERIENCE OF THE REGIONAL CENTRE "GRIGORE ALEXANDRESCU" EMERGENCY CHILDREN'S HOSPITAL - Elena Roxana Smadeanu; Simona Elena Mosescu; Carmen Zapucioiu; Dumitru Oraseanu (Amaltea Medical Publishing House, 2017)
Introduction. The sweat test is the standard method for the diagnosis of cystic fibrosis (CF). The sweat conductivity represents an alternative not yet accepted as a diagnosis method, in spite of its good correlation with chloride (Cl-) titration. The aim of this paper is twofold: to highlight the reference values for this method, as they differ from those used in the case of the Gibson-Cooke method, and also to test the capacity of the conductivity method to discriminate patients with and without CF. Methods. Sweat conductivity was determined for 2,180 patients admitted to the Pulmonology Department of "Grigore Alexandrescu" Emergency Children's Hospital, in Bucharest, between January 2000 and June 2015. The CF diagnosis was determined on the basis of suggestive clinical manifestations, associated with two positive sweat tests (ST) and/or genetic testing. The sweat test was considered positive if the result was higher than 75 mmol/L, as recommended by the producer of the used technology (Wescor). The patients were divided in three groups: the first group - the patients with values ≤45 mmol/L NaCl, the second group - the patients with values between 46 and 65 mmol/L, and the third group - the patients with tested values > 65 mmol/L. The ROC curve was used to determine the threshold value that discriminated patients with and without CF. Results. No patient was determined to suffer from CF in the first category. In the second group, there was one patient with the diagnosis of atypical CF. Eighty patients suffering from CF had values > 65 mmol/L, and among these 80 patients, 79 had values > 75mmol/L. The threshold value for the optimum prediction of the CF diagnosis was thus determined to be 76 mmol/l, with an area under the curve of 0.999, p<0.000, which makes the method excellent in identifying the patients with CF with a sensitivity and specificity of 97%. Conclusion. the values of sweat conductivity are higher than those obtained through Cl- titration, Cl- titration being necessary and compulsory in equivocal cases.